Production of conidia by Peronosclerospora sorghi on sorghum crops in Zimbabwe - Bock, C.H.; Jeger, M.J.; Mughogho, L.K.; Mtisi, E.; Cardwell, K.F. (Wiley, 1998)
Factors affecting the production of conidia of Peronosclerctsporas orghi, causing sorghum downy mildew (SDM), were investigated during 1993 and 1994 in Zimbabwe. In the field conidia were detected on nights when the minimum remperature was in the range l0-19ºC. On 73% of nights when conidia were detected rain had fallen within the previous 72h and on 64% of nights wind speed was < 2.0 m s-1. The time period over which conidia were detected was 2-9h. Using incubated leaf material, conidia were produced in the temperature range 10-26oC. Local lesions and systemically infected leaf material produced 2.4-5.7 x 103 conidia per cm2. Under controlled conditions conidia were released from conidiophores for 2.5h after maturation and were shown to be well adapted to wind dispersal, having a settling velocity of 1.5 x 10-4 m s- 1. Conditions that are suitable for conidia production occur in Zimbabwe and other semi-arid regions of southern Africa during the cropping season.